2011
DOI: 10.1037/a0023287
|View full text |Cite
|
Sign up to set email alerts
|

Assessing decision making in young adult romantic relationships.

Abstract: Romantic relationships among young adults are rich with ambiguity and without a clear, universal progression emphasizing the need for active decision making. Lack of active decision making in romantic relationships can lead to increases in constraints (e.g. pregnancy, shared living space or finances) that promote the continuation of relationships that would have otherwise ended, leading to increased risk of relationship distress. Because there is no available assessment of thoughtfulness regarding relationship… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
73
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
2
1

Relationship

3
6

Authors

Journals

citations
Cited by 49 publications
(77 citation statements)
references
References 41 publications
3
73
1
Order By: Relevance
“…For example, in a study by Owen, Rhodes, and Stanley (2013) individuals who reported having thoughtful decision-making processes also reported more dedication to their partners and higher satisfaction in their relationship. However, on the contrary, Vennum and Fincham (2011) did not find a significant correlation between thoughtful decision-making processes and more dedication in young adult romantic relationships.…”
Section: Introductioncontrasting
confidence: 77%
“…For example, in a study by Owen, Rhodes, and Stanley (2013) individuals who reported having thoughtful decision-making processes also reported more dedication to their partners and higher satisfaction in their relationship. However, on the contrary, Vennum and Fincham (2011) did not find a significant correlation between thoughtful decision-making processes and more dedication in young adult romantic relationships.…”
Section: Introductioncontrasting
confidence: 77%
“…Sliding was assessed with the Deciding subscale of the Relationship Deciding Scale (Vennum & Fincham, ). Participants reported their agreement with statements such as, “With romantic partners I weigh the pros and cons before allowing myself to take the next step in the relationship (e.g., be physically intimate)” and “It is important to make conscious decisions about whether to take each major step in romantic relationships.” Responses ranged from strongly disagree (1) to strongly agree (5); they were coded and summed so that higher scores reflect greater sliding.…”
Section: Methodsmentioning
confidence: 99%
“…Efficacy beliefs have been related to the successful resolution of conflict and a willingness to discuss problems in marriages (Fincham & Bradbury, ). Additionally, relationship efficacy mediated the association between parent's marital conflict and young adult relationship conflict behavior (Cui et al, ) and was associated with fewer negative interactions (Vennum & Fincham, ; Whitton et al, ). Thus, we expect individuals with higher levels of relationship confidence to be motivated to engage in positive relationship interactions, such as problem solving.…”
Section: Theoretical Frameworkmentioning
confidence: 99%